Structures and energies of the transition between two conformations of the alternate frame folding calbindin-D9k protein: a theoretical study1. Issue 81 (3rd September 2015) - Tong, Mingqiong; Wang, Qing; Wang, Yan; Chen, Guangju
<x xml:space="preserve">Abstract</x> We carried out molecular dynamics simulations and energy calculations for the two states of the alternate frame folding (AFF) calbindin-D9k protein and their conformational transition in Ca2+-free form to address their dynamical transition mechanism.